Epidemiology of Burn Injuries in Cipto Mangunkusumo Hospital from 2009 to 2010 - Pujisriyani, Pujisriyani; Wardhana, Aditya (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: Burns are one of the most devastating conditions encountered in medical world. It affects people of all ages, from the very young to the elderly, and represents an assault on all aspects of the patient, from the physical to the psychological.Method: The collection and analysis of burn patients admitted to Cipto Mangunkusumo Burn Centre between January 2009 and December 2010 were studied retrospectively in terms of admissions, age, sex, extent of burn, causes of burns, referral, length of hospital stay (LOS) and mortality. Result: A total of 303 burn patients were admitted with the male to female ratio is 2.26 : 1 and the mean age of admission is 25.7 years (15-54 yr). Most of the patient presented with 20-50% extent of burn (mean 45.87%). The most common cause of burn injury is LPG at 30.4 % followed by flame at 25.7% and by scald at 19.1%. The overall mean LOS and mortality are 13.72 days and 34%. Conclusion : LPG is the major cause of burn and the mortality are 42.4%. Because of level of the mortality, the prevention and management of LPG and the safety of the product of LPG should be given in terms of government regulations.